Peningkatan Ketahanan Keluarga Dalam Menghadapi Pandemi Covid-19 - Rita Eka Izzaty; Siti Rohmah Nurhayati; Farida Harahap; Rosita Endang Kusumaryani; Banyu Wicaksono; Cania Mutia; Fatonah Istikomah; Gayari Jamila Nugrastiti (IAIN AMBON, 2023)
The COVID-19 pandemic has an impact on everyone, including individuals in the family. Covid-19 which is actually causing a crisis in society needs to be overcome by increasing family resilience. Family resilience is a family condition that has tenacity and toughness and contains physical and material abilities to live independently and develop themselves and their families to live harmoniously in increasing physical and spiritual well- being and happiness. Increasing family resilience is carried out so that each family and the individuals in it are able to get through it well. This study will improve family resilience through interventions in the form of psycho education on parent and child attachment to generate hope, as well as mindfulness parenting and continued online consultation through whatsapp group. This study used a sample of 69 participants spread from all over Indonesia. The results of the study indicate that there is a difference significantly in participants' understanding of knowledge before and after participating in online talk shows. Overall, all participants felt that the interventions in the form of psycho education and counseling were satisfying.Keywords: attachment, family resilience, mindfulness parenting, pandemic covid-19